Creating value via the circular economy: Practices in the tourism sector - Mirdaim Axhami; Valentina Ndou; Veronica Milo; Paola Scorrano (Administrative Sciences, 2023)
Among major international research and practice issues, the issue of the circular economy has emerged recently as "an alternative economic paradigm" to address the current needs of the present and to search for innovative solutions for the future. The objective of this paper is to explore the initiatives and practices of the circular economy that could be actuated by tourism firms with the aim of understanding the value that could be created and its contribution to sustainable development based on decarbonization, energy efficiency, and the use of renewable sources. To achieve this objective, an in-depth, qualitative case study of a tourism resort is presented and analyzed to identify the key CE practices activated, with the aim of creating greater value and contributing to sustainable production and consumption. The results show that the main CE practices implemented focus primarily on enhancing resource efficiency, reducing emissions, and minimizing environmental impacts. This research also emphasizes the benefits that the CE provides in terms of economic, environmental, and social efficiency. The study enriches the relevance of CE and the sustainability approach for the tourism sector by highlighting the main value opportunities that tourism firms could grasp from the application of CE. Also, the paper contributes to providing practical suggestions regarding possible initiatives and practices that tourism managers could adopt for deploying CE practices.
Keywords: 350; circular economy; sustainability; tourism sector; value creation